NITROGEN RATES AND RESIDUAL EFFECT OF CO-INOCULATION OF SOYBEAN ON MAIZE PLANTS - Teixeira Ferreira Candido, Aureane Cristina; Camillo de Carvalho, Marco Antonio; Felito, Ricardo Adriano [UNESP]; Rocha, Adriano Maltezo [UNESP]; Yamashita, Oscar Mitsuo (Univ Fed Rural Semi-arido-ufersa, 2020)
Co-inoculation consists of using microorganism combinations with synergic effect that surpass the results obtained with their use alone. The objective of this work was to evaluate the effect of inoculation and co-inoculation on soybean plants, and their residual effect on maize plants grown intercropped with ruzigrass (Urochloa ruziziensis), under different N fertilizer rates. The experiment was conducted at the experimental area of the Mato Grosso State University, Alta Floresta campus, in a Typic Hapludox. A randomized block design was used for the soybean crops; the treatments consisted of Bradyrhizobium japonicum inoculated single, or co-inoculated with Azospirillum brasilense, with 20 replications. A randomized block design in a strip-plot arrangement was used for the winter maize-ruzigrass intercrop (WMRI); the treatments consisted of combination of residual effect of inoculation and co-inoculation in the strips, and five N fertilizer rates (0, 50, 100, 150, and 200 kg ha(-1)) in plots with WMRI, with four replications. The co-inoculation of soybean seeds and its residual effect on the maize crops increased the root dry weight of plants of both crops; however, no increases were found for most vegetative and reproductive characteristics of maize plants. Yield and most characteristics evaluated had increasing linear responses to increases in N rates, indicating the plants could respond to rates above 200 kg ha(-1).
Keywords: Intercrop; Urochloa ruziziensis; Azospirillum brasilense; Nitrogen Fertilization